Detection of Green Mould Rot Infection of Citrus Fruit by X-ray Scanning Non-Destructive Technology - Gadgile, Dhondiram Panditrao; JOSHI, CHANDRAKANT PADMAKAR; SHINDE, VIKAS MADHUKARRAO; KACHARE, PARSHURAM BABARAO (Current Botany, 2017)
ABSTRACT Green mould rot is important post-harvest fungal disease of citrus. It is caused by Penicillium digitatum. To study the detection of fungal infection in citrus fruit by X-ray scanning technique, the spore suspension of Penicillium digitatum was inoculated by sterilized disposable syringe in citrus fruit in aseptic condition.Â Healthy citrus without inoculation was treated as control. Infection of green mould rot was detected by X-ray scanning nondestructive technology. Key words: Penicillium digitatum, Citrus, X-ray scanning, Post-harvest disease. Â